2013
DOI: 10.1017/s1047951113002199
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular dimensions, systolic functions, and mass in term neonates with symmetric and asymmetric intrauterine growth restriction

Abstract: Our study has demonstrated that although neonates with both symmetric and asymmetric intrauterine growth restriction had lower left ventricular dimensions, relative posterior wall thickness, left ventricular mass, and mass index when compared with appropriate for gestational age neonates, left ventricular systolic functions were found to be preserved. In our study, low socio-economic level, short maternal stature, and low maternal weight were found to be risk factors to develop intrauterine growth restriction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Previous studies have shown increased septal thickness in LGA infants or in the presence of maternal diabetes [6][7][8]22 , as well as a thicker left ventricular posterior free wall 23 . Septal hypertrophy has been demonstrated previously in infants that were growth restricted in utero 24 , but smaller ventricular walls have also been reported 25 . In contrast, we found no statistically significant difference between the groups for septal thickness.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown increased septal thickness in LGA infants or in the presence of maternal diabetes [6][7][8]22 , as well as a thicker left ventricular posterior free wall 23 . Septal hypertrophy has been demonstrated previously in infants that were growth restricted in utero 24 , but smaller ventricular walls have also been reported 25 . In contrast, we found no statistically significant difference between the groups for septal thickness.…”
Section: Discussionmentioning
confidence: 64%
“…The ratio of the left ventricular wall thickness to diastolic diameter ("relative wall thickness") has been found to be decreased in infants born growth restricted compared to their AGA peers, indicating dilation of the ventricle (eccentric hypertrophy) (37,39). Another measure that is used to detect ventricle dilation, the left ventricular end diastolic internal diameter, has been found to be greater in infants born growth restricted than in AGA controls (38,40), although this finding has not been consistently reported (6,41).…”
Section: Cardiac Morphologymentioning
confidence: 99%
“…Dilation of the left atrium has been demonstrated by an increased left atrium/aortic root ratio in comparison to AGA controls (26). Cardiac changes in IUGR are thus most often described as cardiomyopathy-like, with dilated ventricles and a more globular cardiac shape compared to controls (10,26,32,34,(37)(38)(39)(40)42). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in the 1990s suggested cardiomegaly as a typical sign of severe FGR, but increased, preserved or decreased cardiac dimensions have also been reported. The presence of myocardial hypertrophy is also controversial, with results suggesting increased, lower or even normal wall thickness. Recently, a more spherical cardiac shape has been reported as a typical feature in FGR.…”
Section: Introductionmentioning
confidence: 99%